(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: To determine knowledge and factors related to knowledge on iron deficiency anemia prevention among pregnant women visiting the Center for Disease Control of Tra Vinh Province (CDC Tra Vinh) in 2022. Methods: A cross-sectional study of 384 pregnant women visiting the CDC Tra Vinh from January 2022 to March 2022. The correct general knowledge about iron deficiency anemia prevention was converted points from the correct questions. Respondents who answered more than 70% of the questions in each section were considered to have the correct knowledge. Results: Among the 384 pregnant women, the correct general knowledge of pregnant women about iron deficiency anemia prevention was limited (accounting for 58.3%). 71.4% of them get information on iron deficiency anemia prevention from health workers (82.1%); Internet, radio (59.1%); friends, collaborators (30.7%). The source of information that pregnant women most want to receive was from health workers (96.1%) and the internet (90.4%). Conclusion: Knowledge of iron deficiency anemia prevention among pregnant women visiting CDC Tra Vinh was limited.